Students' Ontogenic and Epistemological Obstacles on the Topic of Pyramid Volume - Sita Mujahidah, Anisah; Rosjanuardi, Rizky (KnE Social Sciences, 2024)
The concept of pyramid volume has been studied at the starting of the elementary school (SD) level and studied more deeply in junior high school (SMP). However, many students make mistakes in solving problems related to the volume of pyramids. This study aims to identify the ontogenic and epistemological obstacles of students in understanding the concept of pyramid volume. This is a qualitative research using a Didactical Design Research (DDR). Sixteen students of grade IX in Bandung who had studied the concept of pyramid volume participated in the study. Data were obtained by analyzing respondents’ ability tests and interviews to solve problems related to the volume of pyramids. Characteristics of ontogenic and epistemological obstacles were found in students’ knowledge in solving problems related to the concept of pyramid volume. The results showed that students experienced several ontogenic and epistemological obstacles which resulted in errors in problem-solving. Keywords: epistemological obstacles, pyramid volume, students’ ontogenic